Self-energy effects on nuclear magnetic resonance parameters within quantum electrodynamics perturbation theory - Romero, Rodolfo Horacio (2002)
A theory for the calculation of self-energy corrections to the nuclear magnetic parameters is given in this paper. It is based on the S-matrix formulation of bound-state quantum electrodynamics (QED). Explicit expressions for the various terms of the S-matrix are given. The interpretation of the self-energy, one- and two vertex terms and some perspective for possible future developments are discussed